Actitudes hacia el enfermo mental - Rodriguez Kauth, Angel (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The purpose of this study was the investigation o f attitudes toward mental patients. Likert scales were administered to two random samples matched on age, sex, place o f residence, occupation and education. Item analyses were carried out using discriminative power and point-biserial correlation procedures. No significant differences in attitude toward mental patients were found between subjects with relatives who were hospitalized in mental institutions and matched Controls.